Functional Development of Fronto-Striato-Parietal Networks Associated with Time Perception - Smith, Anna; Giampietro, Vincent; Brammer, Mick; Halari, Rozmin; Simmons, Andrew; Rubia, Katya (Frontiers in Human Neuroscience, 2011)
Compared to our understanding of the functional maturation of executive functions, little is known about the neurofunctional development of perceptive functions. Time perception develops during late adolescence, underpinning many functions including motor and verbal processing, as well as late maturing higher order cognitive skills such as forward planning and future-related decision-making. Nothing, however, is known about the neurofunctional changes associated with time perception from childhood to adulthood. Using functional magnetic resonance imaging we explored the effects of age on the brain activation and functional connectivity of 32 male participants from 10 to 53 years of age during a time discrimination task that required the discrimination of temporal intervals of seconds differing by several hundred milliseconds. Increasing development was associated with progressive activation increases within left lateralised dorsolateral and inferior fronto-parieto-striato-thalamic brain regions. Furthermore, despite comparable task performance, adults showed increased functional connectivity between inferior/dorsolateral interhemispheric fronto-frontal activation as well as between inferior fronto-parietal regions compared with adolescents. Activation in caudate, specifically, was associated with both increasing age and better temporal discrimination. Progressive decreases in activation with age were observed in ventromedial prefrontal cortex, limbic regions and cerebellum. The findings demonstrate age-dependent developmentally dissociated neural networks for time discrimination. With increasing age there is progressive recruitment of later maturing left hemispheric and lateralised fronto-parieto-striato-thalamic networks, known to mediate time discrimination in adults, while earlier developing brain regions such as ventromedial prefrontal cortex, limbic and paralimbic areas and cerebellum subserve fine-temporal processing functions in children and adolescents.